The Effect of Exercise Methods and Leg Muscle Power on Agility Badminton Player at PB Satria Club Tegal Regency in 2021 (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
Agility is a very important component in the game of badminton. Leg muscle power is a factor that affects agility. Less varied agility training methods will have an impact on performance that has not been maximized. This study aims to analyze the 4-corner shuttle run training method and shadow and leg muscle power on agility in PB Satria players, Tegal Regency. This study uses a quantitative approach. The research design used is a quasi-experimental design with a 2x2 factorial design. The sample in this study was the male players of PB Satria, Tegal Regency, totaling 20 people. The data collection instrument is the 4-corner shuttle run and shadow training method and the measurement of leg muscle power. The data analysis technique used two-way variance (Two Way Anova). The results of this study are as follows: (1) the results of the calculation of the variable method of the 4-corner shuttle run and shadow training method obtained a sig value of 0.001 < 0.05 (2) the results of the calculation of the high leg muscle power variable and low leg muscle power obtained a sig value of 0.004 < 0.05 (3) the results of testing the interaction between the training method and leg muscle power obtained a sig value of 0.052 > 0.05. The conclusions based on the results of this study are (1) there are differences in the effect of the 4-corner shuttle run training method sample and the shadow training method on agility (2) there is a difference in the effect between samples of high leg muscle power and low leg muscle power on agility (3) there is no interaction between training methods and leg muscle power on agility.